ANALISIS STRATEGIS PUBLIC RELATIONS DI PT X - Feriska Nia Mulani; Christian Wiradendi Wolor; Eka Dewi Utari (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This research aims to analyze the strategic role of Public Relations (PR) at PT X in building the company's image, maintaining relationships with stakeholders, and supporting business objectives through internal and external communication management. Using a qualitative approach through interviews, literature studies, and document analysis, it was found that PT X implements PR strategies such as media relations, event marketing, CSR, digital PR, and crisis management to maintain the company's reputation. As a result, PR contributes to strengthening customer loyalty, brand awareness, and public trust, and becomes a reference for other finance companies in optimizing PR as a sustainable business strategy.